Symbiotic nitrogen fixation of Dimorphandra macrostachya in forests of Venezuelan Guayana Highland - Méndez, Carlos; Bilbao, Bibiana (BOSQUE, 2017)
To test the hypothesis that the availability of soil inorganic nitrogen controls the nitrogen fixation per D. macrostachya plant, in this work the variation of biological nitrogen fixing by D. macrostachya was measured along the distance from the forest-savanna boundary to the forest inside, in a gradient of soil inorganic nitrogen, at two riverine forests of the Gran Sabana. Biological nitrogen fixing increased from the inner forest (2-8 kg ha-1 year-1) to the forest-savanna boundary (15-35 kg ha-1 year-1), depending on plant density that decreased from the forest boundary (1,178 plants ha-1 ) to forest inside (664 plants ha-1 ) and was not correlated to inorganic nitrogen soil concentration. Our results suggest that, contrary to the generally observed trend, biological nitrogen fixing is regulated by factors other than soil inorganic nitrogen as light environment and phosphorus availability.